2017
DOI: 10.1249/mss.0000000000001318
|View full text |Cite|
|
Sign up to set email alerts
|

Calculated versus Measured MVV—Surrogate Marker of Ventilatory Capacity in Pediatric CPET

Abstract: The measured MVV was significantly lower than the calculated MVV in our pediatric subjects. The calculated MVV was a better surrogate of maximum ventilatory capacity as shown by significant correlation to other ventilatory parameters during CPET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Her MVV estimated by Kennedy equation (1953) would be increased by 15.38 L/min (3.56 times 40 vs. 3.56 times 35.68), that is, 12%. Such an increase would reduce the diagnostic potential of CPET with an imprecise determination of ventilatory limitation defined as ventilatory reserve < 20% MVV (Colwell & Bhatia, 2017). An overestimation of MVV value would thus lead to an erroneous exclusion of a diagnosis of ventilatory limitation in individuals.…”
Section: T a B L E 2 Correlation Between Spirometric Parameters And Amentioning
confidence: 99%
See 2 more Smart Citations
“…Her MVV estimated by Kennedy equation (1953) would be increased by 15.38 L/min (3.56 times 40 vs. 3.56 times 35.68), that is, 12%. Such an increase would reduce the diagnostic potential of CPET with an imprecise determination of ventilatory limitation defined as ventilatory reserve < 20% MVV (Colwell & Bhatia, 2017). An overestimation of MVV value would thus lead to an erroneous exclusion of a diagnosis of ventilatory limitation in individuals.…”
Section: T a B L E 2 Correlation Between Spirometric Parameters And Amentioning
confidence: 99%
“…In practice, the MVV is measured over 12 s and then extrapolated to one minute to overcome the difficulties (shortness of breath, fatigue, dizziness) that a subject may encounter during the measurement process, which can often be tedious and time‐consuming (Colwell & Bhatia, 2017; Kennedy, 1953). Better still, these difficulties led several authors to develop and use an equation to estimate its value based on maximum volume of air exhaled during the first second of forced expiration (FEVı) following maximum inspiration: MVV = FEVı × 35 (Gandevia & Hugh‐Jones, 1957) FEVı × 37.5 (Cara, 1953) or MVV = FEVı × 40 (Kennedy, 1953) are among the most common in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal voluntary ventilation (MVV) is the largest amount of air that a person can inhale and then exhale during a 12to 15-s interval with maximal voluntary effort (Neder et al, 1999). This maneuver was used to provide information about the functioning of the inspiratory pump and chest wall and is used to evaluate maximum ventilatory capacity (Colwell and Bhatia, 2017) and respiratory muscle endurance, but the last ERS statement on respiratory muscle tests does not recommend its use for these purposes because mechanical aspects of the chest wall and lung tissue can affect the MVV value (Laveneziana et al, 2019). It is used for indirect calculation of the ventilatory reserve through a relationship with minute volume during a maximum exercise test (ATS/ACCP, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Fulton et al (1995) found that MVV was similar to the proxy measure of MVV viz 35⋅FEV 1 in healthy African–American, adolescent girls. Furthermore, a recent study found that conclusions from test results depend on which surrogate for MVV is chosen only compounds interpretation challenges (Colwell and Bhatia, 2017). Taken together, it is not at all clear whether directly measured MVV or multiples of FEV 1 as proxies for MVV reflect EFL and therefore ventilatory limitation during exercise in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%